2019
DOI: 10.1155/2019/6196532
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Impacts of Diabetes on the Susceptibility of Mycobacterium tuberculosis

Abstract: The interaction between diabetes and major world infections like TB is a major public health concern because of rapidly rising levels of diabetes. The dual burden of tuberculosis (TB) and diabetes mellitus (DM) has become a major global public health problem. Diabetes mellitus is a major risk factor for the development of active and latent tuberculosis. Immune mechanisms contributing to the increased susceptibility of diabetic patients to TB are due to the defects in bacterial recognition, phagocytic activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 70 publications
3
113
1
9
Order By: Relevance
“…25 Nevertheless, the downturn of TB morbidity starts to retard to be falling at 2.613% per year since 2015, which may be ascribed to the continuously upsurged drug-resistant TB, the increased floating population and the coinfections of HIV-TB as well as other TB-related comorbidities such as influenza, diabetes and hypertension, and the like in recent years. 1,7,8 Further, we used the ETS framework to estimate the TB incidence into future until 2035, indicating that TB incidence rate will continue to descend at about 2.613% per year between 2019 and 2035. But such a rate of decline in TB incidence being reached falls far short of what is required to achieve the WHO's milestones for 2020 and 2025 and targets for 2030 and 2035.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Nevertheless, the downturn of TB morbidity starts to retard to be falling at 2.613% per year since 2015, which may be ascribed to the continuously upsurged drug-resistant TB, the increased floating population and the coinfections of HIV-TB as well as other TB-related comorbidities such as influenza, diabetes and hypertension, and the like in recent years. 1,7,8 Further, we used the ETS framework to estimate the TB incidence into future until 2035, indicating that TB incidence rate will continue to descend at about 2.613% per year between 2019 and 2035. But such a rate of decline in TB incidence being reached falls far short of what is required to achieve the WHO's milestones for 2020 and 2025 and targets for 2030 and 2035.…”
Section: Discussionmentioning
confidence: 99%
“…6 At present, the slow fall in TB morbidity in China is attended by the increasing drug-resistant TB, TB-HIV dual infection, population movement, and other TB-related comorbidities such as influenza, diabetes, and hypertension, etc., these may result in a risk of recurrence in TB incidence. 1,7,8 Therefore, to be on track to achieve the WHO's goals during different periods, accurate projection for the long-term seasonality and trends of TB epidemics will be significantly valuable for guiding emergency preparedness and decision-making process of TB control.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired immune response and intracellular bacterial killing have the potential to increase the burden of bacteria, chronic inflammation, and central necrosis, which facilitates the spread of bacteria and miliary TB. 54 Although not much studied, other than DM, hepatitis infection is also comorbidity to TB. Findings from a previous study by Wu in Taiwan showed that the incidence of active TB is higher in HCV infections than the controls (134.1 vs. 89.1 per 100,000 personyear; incidence rate ratio=1.51; p=0.014).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of the Kombewa HDSS, acute cardiac disease was the primary cause of 1.9% of deaths, unspeci ed cardiac disease was the cause of 3.1% of deaths, stroke was the cause 5.2% of deaths, renal disease was the cause of 1.2% of deaths [14]. Additionally, diabetes weakens the immune system and makes people more susceptible to bacterial infections, such as lower respiratory infections, urinary tract infections, fungal infections, and tuberculosis [21,22,27]. In the Kombewa HDSS, acute respiratory infection (including pneumonia) was the cause of 10.1% of deaths, pulmonary tuberculosis was the cause of 4.9% of deaths, and sepsis was the cause of 0.2% of deaths.…”
Section: Discussionmentioning
confidence: 99%